PENGARUH MEDIA ANIFONE TERHADAP PENGENALAN KOSAKATA BAHASA INGGRIS PADA ANAK DI TAMAN KANAK-KANAK NEGERI PEMBINA TIGO NAGARI KABUPATEN PASAMAN - Nur Afni Oktafia; Elise Muryanti; Rismareni Pransiska; Saridewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
English language introduction to early childhood needs to be stimulated by introducing simple vocabulary so that it is easy for children to understand. The increasingly rapid development of science and technology requires the next generation of the nation to compete both at the national and global levels, which is required to have English language skills. This makes English language introduction to early childhood important to children. Many children experience difficulties in learning English vocabulary at the Pembina Tigo Nagari State Kindergarten, Pasaman Regency, which has not developed according to their age, as well as the lack of children's involvement in learning English using interesting media. This problem indicates that the introduction of English vocabulary in learning needs to be designed to be more interesting and effective for children. The type of research used is quantitative research with an experimental method. The population in this study amounted to 40 children. The research design used a quasi-experimental with a purposive sampling technique, namely sampling based on certain considerations needed for the research. Hypothesis testing in this study used a Paired Sample T-test with a significance level of 0.05. The results of this study indicate that the use of ANIFONE media has an effect on introducing English vocabulary to early childhood students at Pembina Tigo Nagari State Kindergarten. This is evidenced by the increase in learning outcomes seen from the pre-test and post-test scores. In addition, the sig value (2-tailed) = 0.005.